The characterization and regulation of the Akt isoforms in breast cancer - Santi, Stacey A (University of Ottawa (Canada), 2009)
Akt/PKB (protein kinase B) is a serine-threonine kinase involved in the regulation of many cellular processes, such as proliferation, metabolism, and cell survival. The elevated activation of the PI3K-Akt (phosphatidylinositol-3 kinase/Akt) pathway has been associated with tumor progression and increased tumour aggressiveness. Akt consists of three isoforms; Akt1, Akt2 and Akt3 (PKBalpha, PKBbeta, and PKBgamma, respectively) which share high similarity at the amino acid level (∼80%). Due to their similarity, it is generally assumed that the three isoforms regulate the same cellular processes, as well as signal to the same downstream substrates with similar preference. However, accumulating lines of evidence now suggest that the isoforms may regulate different cellular processes and are not functionally redundant. To further study the Akt isofonns and the role they play in the progression of tumorigenesis, a model of breast cancer (MDA-MB231 cell line) was employed. The Akt isoforms were first characterized through the examination of their subcellular localization to discern if differences in functional regulation can be inferred through their localization. The data obtained from this work demonstrated that isoforms displayed differential subcellular localizations. Specifically, Akt2 was found co-localized with the mitochondria, while Akt3 resided in the nucleus, thereby challenging the accepted notion that the isoforms are localized only in the cytoplasm. Next, studies were undertaken to determine which isoform is most important for cancer cell survival. Akt2 as found to be the most important isoform for survival in MDA-MB231 cells. Targeted ablation of each isoform using siRNA showed that Akt2 regulated cancer cell proliferation specifically by promoting cell cycle progression via the regulation of Cdk2, p27 and cyclin D. In addition, Akt2 ablation inhibited activation of the mTOR pathway through the downregulation of p70S6K. Prolonged inhibition of Akt2 altered mitochondrial morphology and eventually led to autophagy of the mitochondria (mitophagy). Collectively, the results of these studies impart a distinct role for Akt2 in cancer cell progression and survival and provide evidence that Akt2 may be a relevant target for future cancer therapies.
Keywords: Chemistry, Biochemistry.